A Systematic Literatur Review (SLR): Picture Books on the Speaking Skills of Elementary School Students - Rizkiyah, Maulidah; Wisudawati, Asih Widi (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This literature review is motivated by the fact that students' speaking skills in elementary schools are still relatively low. Speaking skills are very necessary for elementary school students, to increase their self-confidence. This review aims to identify the influence of picture storybooks on speaking skills in elementary school students. This review uses a systematic literature review method using PRISMA, which was carried out on 23 articles obtained from Google Scholar via Publish or Perish. Keywords in the article search are "speaking skills," "speaking skills of elementary school students," and "picture story books." The results of this review are that picture story books are proven to significantly improve students' speaking fluency and make them more confident in telling stories. Students who initially felt embarrassed or afraid of making a mistake became braver in trying to tell the story again because interesting visuals supported it. The implications of mastering speaking skills since elementary school have a long-term impact on student development, both in academic, social, and community life. The conclusion from this literature study is that picture storybooks influence elementary school students' speaking skills. The recommendation of this literature review is that picture storybooks can be used as alternative learning media used in the learning process.